Evaluating the Role of ISO Standards in Enhancing the Performance of Medical Laboratories - Alali, Mishary Mohammad Mostafa; Albalawi, Muteb Sulaiman Hamdan; Alshehri , Ahmad Salem Ahmad; Ghazwani , Abdullah Msoud Mofareh; Alghamdi, Mohammed Ali Mohammed; Albalawi , Malak Mohammed Dohbyan; Alahmari, Naif Ali Suhaim; Alatawi, Ahmed Ameen Salman; Alfuhaymani , Ayed Rahil Muhji; Alatawi, Naif Furayj Saeed (Journal of Ecohumanism, 2024)
The role of ISO standards in enhancing the performance of medical laboratories has become increasingly significant in ensuring quality and reliability in healthcare services. This review evaluates the impact of ISO standards, particularly ISO 15189, on the operational efficiency, diagnostic accuracy, and risk management of medical laboratories. It highlights the key components of these standards, including quality management systems, personnel competence, and continuous improvement, and examines their contributions to patient safety and institutional credibility. The article also explores the challenges of implementing ISO standards, such as financial constraints and resistance to change, and proposes strategies to overcome these barriers. The findings underscore the importance of ISO standards in promoting a culture of quality and innovation within medical laboratories, ultimately improving healthcare outcomes.